2022
DOI: 10.1111/anae.15834
|View full text |Cite
|
Sign up to set email alerts
|

Novel wearable and contactless heart rate, respiratory rate, and oxygen saturation monitoring devices: a systematic review and meta‐analysis

Abstract: We performed a systematic review and meta-analysis to identify, classify and evaluate the body of evidence on novel wearable and contactless devices that measure heart rate, respiratory rate and oxygen saturations in the clinical setting. We included any studies of hospital inpatients, including sleep study clinics. Eighty-four studies were included in the final review. There were 56 studies of wearable devices and 29 of contactless devices. One study assessed both types of device. A high risk of patient selec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 82 publications
0
13
0
Order By: Relevance
“…Studies on the use of fitness trackers in a perioperative setting or among patients with multiple pre-existing diseases are rare [ 12 ] and, according to systematic reviews, also hampered by a high risk of bias [ 13 ] and suffer from low quality [ 14 ]. In particular, it has been shown that motion artifacts influence the mean absolute error (MAE) of the measurements by up to 30% [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies on the use of fitness trackers in a perioperative setting or among patients with multiple pre-existing diseases are rare [ 12 ] and, according to systematic reviews, also hampered by a high risk of bias [ 13 ] and suffer from low quality [ 14 ]. In particular, it has been shown that motion artifacts influence the mean absolute error (MAE) of the measurements by up to 30% [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, counseling with reassurance but education about very low frequency outcomes would allow parents to pursue low-cost monitoring strategies. [47][48][49][50] Among children ages 1-4 years, SUDC is more than 2 times as common as deaths due to house fires (~100 case/year), and about half as common as drownings (~475 deaths/year), yet public education for both fire prevention and water accidents is commonplace, whereas SUDC education is not. 8,47,51 Febrile seizures are not considered epilepsy but may be the first presentation of an epilepsy syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…We should consider developing low-cost monitoring/alarming systems to reduce the frequency of these deaths, similar to efforts in SUDEP prevention. 48,49,50,52 Understanding genetic, biologic, and environmental factors that predispose a child's brain to febrile seizures may help distinguish adverse outcomes from pathogenesis. Genetic factors identified in genome-wide association studies related to fever response and neuronal excitability may represent biomarkers, as well as collaborative studies of SUDEP and SUDC.…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta‐analysis by Chan et al. suggests that wearable devices may offer acceptable accuracy and precision in monitoring, though high quality studies are still needed [6].…”
Section: Figurementioning
confidence: 99%
“…McFarlane et al and Perez et al have supported using smartwatches in critical care settings and to detect asymptomatic episodes of atrial fibrillation [3,4], and utility in the early detection of COVID-19 has also been described [5]. A recent meta-analysis by Chan et al suggests that wearable devices may offer acceptable accuracy and precision in monitoring, though high quality studies are still needed [6].…”
mentioning
confidence: 99%